2004
DOI: 10.1242/jcs.01411
|View full text |Cite
|
Sign up to set email alerts
|

Increased internalisation and degradation of GLT-1 glial glutamate transporter in a cell model for familial amyotrophic lateral sclerosis (ALS)

Abstract: It has been suggested that glutamate-induced excitotoxicity plays a central role in the development of motor neuron diseases such as amyotrophic lateral sclerosis (ALS). The GLT-1 isoform of the glutamate transporter gene family is the most important transporter involved in keeping extracellular glutamate concentration below neurotoxic levels. Its loss and an increase in extracellular glutamate has been documented in cases of sporadic and familial ALS, as well as in animal models expressing ALS-linked Cu2+-Zn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 49 publications
2
46
0
2
Order By: Relevance
“…Our data now reveal interesting similarities between SN1 regulation and mechanisms involved in the regulation of the glial glutamate transporter GLT and glutamate-aspartate transporter GLAST: PMA-induced activation of PKC also stimulates internalization of the glial glutamate transporters GLT and GLAST (Kalandadze et al, 2002;Vanoni et al, 2004;Guillet et al, 2005). Furthermore, coimmunoprecipitation of GLT and PKC␣ has been demonstrated (Gonzalez et al, 2005).…”
Section: Functional Implications Of Sn1 Phosphorylationmentioning
confidence: 56%
“…Our data now reveal interesting similarities between SN1 regulation and mechanisms involved in the regulation of the glial glutamate transporter GLT and glutamate-aspartate transporter GLAST: PMA-induced activation of PKC also stimulates internalization of the glial glutamate transporters GLT and GLAST (Kalandadze et al, 2002;Vanoni et al, 2004;Guillet et al, 2005). Furthermore, coimmunoprecipitation of GLT and PKC␣ has been demonstrated (Gonzalez et al, 2005).…”
Section: Functional Implications Of Sn1 Phosphorylationmentioning
confidence: 56%
“…These studies suggest that at least a portion of internalized GLT-1 is targeted for degradation after internalization. Others have shown that GLT-1 can be internalized in to co-expression with the variant of superoxide dismutase associated with amyotrophic lateral sclerosis (Vanoni et al, 2004). It will be interesting in future studies to determine if the cellular machinery contributing to phorbol esterdependent internalization of GLT-1 also mediate internalization caused by this or other stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…Increasing evidence show that the dysfunctions in endocytosis are common themes in many neurological disorders, especially neurodegenerative diseases (Cataldo et al, 2000;Nixon, 2005;Smith et al, 2005;Vanoni et al, 2004), thus interference of abnormal endocytosis may be potential therapeutic strategies in neurological disease. Our study demonstrates that syntaxin 1A is an intrinsic regulator of KAinduced EAAC1 endocytic sorting.…”
Section: Discussionmentioning
confidence: 99%